Sustainable flood memories, lay knowledges and the development of community resilience to future flood risk. Issue 1 (22nd September 2016) - McEwen, Lindsey; Garde‐Hansen, Joanne; Holmes, Andrew; Jones, Owain; Krause, Franz
Abstract : The paradigm shift to more distributed flood risk management strategies in the UK involves devolved responsibilities to the local, and the need to enhance risk ownership by communities. This poses questions about how communities build resilience to future flood risk, and how agencies support these processes. This paper explores results from interdisciplinary research on 'sustainable flood memory' in the context of effective flood risk management as a conceptual contribution to a global priority. The project aimed to increase understanding of how flood memories provide a platform for developing and sharing lay knowledges, creating social learning opportunities to increase communities' adaptive capacities for resilience. The paper starts by conceptually framing resilience, community, lay knowledge and flood memory. It then explores key themes drawn from semi‐structured interviews with floodplain residents affected by the UK summer 2007 floods in four different settings, which contrasted in terms of their flood histories, experiences and kinds of 'communities'. Sustainable flood memories were found to be associated with relational ways of knowing, situated in emotions, changing materiality and community tensions. These all influenced active remembering and active forgetting. The paper reflects on varying integrations of memory, lay knowledges and resilience, and critically evaluates implications of the sustainable flood memory concept for the strategy, process and practice of developing community flood resilience. Given the concept's value and importance of 'memory work', the paper proposes a framework to translate the concept practically into community resilience initiatives, and to inform how risk and flood experiences are communicated within communities.